Behind bilirubin neurotoxicity: discovering what’s left at the blood-brain barrier - Palmela, Inês Maria Simões, 1985- (2013)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2013